2007
DOI: 10.1016/j.cell.2007.11.026
|View full text |Cite
|
Sign up to set email alerts
|

The Exoneme Helps Malaria Parasites to Break out of Blood Cells

Abstract: Malaria parasites must invade the erythrocytes of its host, to be able to grow and multiply. Having depleted the host cell of its nutrients, the parasites break out to invade new erythrocytes. In this issue of Cell, Yeoh et al. (2007) discover a new organelle, the exoneme, that contains a protease SUB1, which helps the parasite to escape from old erythrocytes and invade new ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The subtilisin-like serine protease PfSUB1 is thought to have an essential function, since a gene deletion attempt was unsuccessful, which is in line with the observation that pharmacological inhibition of PfSUB1 activity blocks egress and ablates the invasive capacity of merozoites [48]. PfSUB1 localises to dense granule-like structures, termed exonemes, which are present at the apical end of the individual merozoite [51]. Prior to egress, PfSUB1 is discharged into the PV lumen, where it is believed to mediate proteolytic activation of a family of papain-like serine rich antigen proteases (SERAs), which have further roles in completing the egress cascade [48].…”
Section: Potential Molecular Mechanisms Regulated By Pfpkgmentioning
confidence: 73%
“…The subtilisin-like serine protease PfSUB1 is thought to have an essential function, since a gene deletion attempt was unsuccessful, which is in line with the observation that pharmacological inhibition of PfSUB1 activity blocks egress and ablates the invasive capacity of merozoites [48]. PfSUB1 localises to dense granule-like structures, termed exonemes, which are present at the apical end of the individual merozoite [51]. Prior to egress, PfSUB1 is discharged into the PV lumen, where it is believed to mediate proteolytic activation of a family of papain-like serine rich antigen proteases (SERAs), which have further roles in completing the egress cascade [48].…”
Section: Potential Molecular Mechanisms Regulated By Pfpkgmentioning
confidence: 73%
“…Recently, PfPKG was reported to regulate the initiation of the proteolytic cascade prior to egress that involves the subtilisin-like serine protease 1 (PfSUB1) [13]. PfSUB1 is maximally expressed in late P. falciparum blood stage schizonts [14] and localises to dense granule-like structures, termed exonemes, that are present at the apical end of the individual merozoite [15]. Prior to egress, PfSUB1 is discharged into the parasitophorous vacuole, where it proteolytically cleaves the serine repeat antigens (PfSERAs) and components of the merozoite surface protein 1 (PfMSP1) complex [14], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Next step involves the high affinity attachment between the apical end of the merozoites and erythrocytes, resulting in the formation of a moving junction. Finally the merozoite invagination into the erythrocyte occurs via formation of a parasitophorous vacuole. Merozoite invasion is orchestrated by proteins released from its apical secretory organelles  micronemes, rhoptries, and dense granules including exonemes . At the time of invasion, these proteins are released in a timely and spatially coordinated manner to facilitate parasite release, its invasion into the erythrocyte and formation of parasitophorous vacuole in which the parasite resides after invasion. Studies in Toxoplasma have demonstrated that micronemes secrete their contents first, followed by secretion from rhoptries and dense granules…”
Section: Introductionmentioning
confidence: 99%